EXPLORING THE RICH TAPESTRY OF JAMBI MALAY TRADITION AND CULTURE: A COMPREHENSIVE STUDY OF KOMPANGAN IN JAMBI SEBERANG - Abdullah Haidar; Evania Herindar; Fauziah Chairiyati; Nur Hendrasto (Jurnal komunikan, 2023)
The purpose of this research is to explain the history of Kompangan as a musical instrument and the roles of Ulu Gendong Group in preserving the Kompangan as traditional Malay arts in Jambi Seberang. By using anthropological research, the results of this study indicate that Kompangan art is Malay Islamic culture and traditional musical of Jambi Province especially from Jambi Seberang. Kompangan have been brought by immigrants from the Middle East. Sambilan Group was founded in Kampung Tengah, Jambi, and that is where Kompangan got its start. Kompangan art has evolved in several districts one of them in Ulu Gedong. Ulu Gedong, Riyatul Jannah, Riyatul Abedin, and Al-Hidayah are the four main compangan groups that make up from Ulu Gedong. Young generation play a crucial role in the preservation of Kompang in Jambi Seberang. The goal for the next generation will value their culture more and keep their cultural legacy alive, particularly this Kompangan art.